Cancer Stem-Like Cells in a Case of an Inflammatory Myofibroblastic Tumor of the Lung - Masciale, Valentina; Grisendi, Giulia; Banchelli, Federico; D'Amico, Roberto; Maiorana, Antonino; Sighinolfi, Pamela; Brugioni, Lucio; Stefani, Alessandro; Morandi, Uliano; Dominici, Massimo; Aramini, Beatrice (Frontiers in Oncology, 2020)
Background. Inflammatory myofibroblast tumor (IMT) is a rare tumor with obscure etiopathogenesis in which different inflammatory cells and myofibroblastic spindle cells are seen histologically. Although the majority of these neoplasms have a benign clinical course, the malignant form has also been reported. The gold standard is the surgical treatment for the complete removal. Our report describes a 50-year-old woman undergone surgery for IMT of the lung. The aim is to determine whether cancer stem cells may be present in IMT of the lung. Methods. In April 2018, the patient underwent surgery for the tumor mass asportation through lateral thoracotomy. The histology of the tumor was consistent with IMT of the lung. The ALDEFLUOR assay, after tissue digestion, was used to identify and sort human lung cancer cells expressing high and low aldehyde dehydrogenase (ALDH) activity. SOX2, NANOG, OCT-4, and c-MYC positivity was additionally determined by immunohistochemistry. Results. The specimen contained 1.10% ALDHhigh cells among all viable lung cancer cells, which indicates population of cancer stem cells is not negligible. Immunohistochemistry assessed cell positivity for ALDH1A1, SOX2, , NANOG, OCT-4, and c-MYC , considered as lung cancer stem-like cells markers. Conclusion. For the first time, we demonstrated the presence of cancer stem cells in a case of IMT of the lung. This finding may provide a base for considering new pathological and molecular aspects of this tumor. This perspective suggests further studies to understand the possibility of developing recurrence depending of the presence of cancer stem cells.